2011
DOI: 10.1021/nn202910t
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Free-Standing Epitaxial Graphene on SiC (0001) by Fluorine Intercalation from a Molecular Source

Abstract: We demonstrated a novel method to obtain charge neutral quasi-free-standing graphene on SiC (0001) from the buffer layer using fluorine from a molecular source, fluorinated fullerene (C(60)F(48)). The intercalated product is stable under ambient conditions and resistant to elevated temperatures of up to 1200 °C. Scanning tunneling microscopy and spectroscopy measurements are performed for the first time on such quasi-free-standing graphene to elucidate changes in the electronic and structural properties of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
79
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 48 publications
(81 reference statements)
9
79
0
Order By: Relevance
“…It was shown that fluorine intercalation only occurred on the buffer layer regions, with the monolayer graphene unaffected by the decomposition of the C 60 F 48 . 23 As we are dealing here with a uniform MLG sample, and no heating of the substrate was performed after C 60 F 48 deposition, we are convinced that the p-type doping observed in this study is a result of surface charge transfer between the graphene and the molecular overlayer, and not due to a modification of the graphene/SiC interface. This view is strengthened by a quantitative description of the doping process which we turn to now.…”
Section: -mentioning
confidence: 53%
“…It was shown that fluorine intercalation only occurred on the buffer layer regions, with the monolayer graphene unaffected by the decomposition of the C 60 F 48 . 23 As we are dealing here with a uniform MLG sample, and no heating of the substrate was performed after C 60 F 48 deposition, we are convinced that the p-type doping observed in this study is a result of surface charge transfer between the graphene and the molecular overlayer, and not due to a modification of the graphene/SiC interface. This view is strengthened by a quantitative description of the doping process which we turn to now.…”
Section: -mentioning
confidence: 53%
“…9 The minimum at zero bias is characteristic of two-dimensional electronic systems. The other minimum located 0.4 eV below the Fermi level (occupied states, positive tip bias) refl ects the position of the Dirac point.…”
Section: Dispersion Relationsmentioning
confidence: 99%
“…3,4 To date, many STM studies have been carried out on graphene. [5][6][7][8][9] Because of its atomic resolution, STM is able to probe important local physical and electronic details of both pristine and modifi ed epitaxial graphene that other techniques are unable to access. In this review, we fi rst introduce the basic working principles and setups used for STM and scanning tunneling spectroscopy (STS).The capabilities of STM/STS are then illustrated by instructive examples of epitaxial graphene characterization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Formation of quasi freestanding graphene is then possible by H and F intercalation between the buffer layer and substrate. 7,8 In the last few years, huge efforts have been undertaken to understand the electronic, structural, and magnetic properties of intercalated graphene systems both with and without the substrate. [9][10][11][12][13] Intercalation of Si is particularly interesting due to the fact that this material forms the basis of modern electronics technology.…”
Section: Introductionmentioning
confidence: 99%